2017
DOI: 10.1055/s-0043-107783
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum Antioxidant Capacity in Healthy Normal Weight and Asymptomatic Overweight Adults

Abstract: Obesity and overweight are major contributors to the burden of chronic disease. Both are defined as abnormal or excessive fat accumulation and by increased production of free radicals leading to oxidative stress. The aim of the present study was to evaluate whether overweight and fat accumulation is associated with serum total antioxidant capacity (TAC) in men and women, irrespective of nutritional habits, nutrient intakes, physical activity, smoking, and other confounders, which may be responsible for modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…The nonobese individuals were younger than the obese individuals (mean ± SEM, 95% CI: 23.0 ± 0.643, 21.7-24.4 vs. 29.0 ± 1.11, 26.7-31.3; P < 0.001). Participants in the obese group showed significantly elevated BMI, waist/hip ratio, WBC counts, hemoglobin A1C, erythrocyte sedimentation rate, and blood pressure compared with the nonobese group, which aligns with other studies involving obese participants (Table 1) (18)(19)(20). One adverse event occurred due to local swelling at the site of the vaccine injection, which resolved within 2 weeks.…”
Section: Participantssupporting
confidence: 86%
“…The nonobese individuals were younger than the obese individuals (mean ± SEM, 95% CI: 23.0 ± 0.643, 21.7-24.4 vs. 29.0 ± 1.11, 26.7-31.3; P < 0.001). Participants in the obese group showed significantly elevated BMI, waist/hip ratio, WBC counts, hemoglobin A1C, erythrocyte sedimentation rate, and blood pressure compared with the nonobese group, which aligns with other studies involving obese participants (Table 1) (18)(19)(20). One adverse event occurred due to local swelling at the site of the vaccine injection, which resolved within 2 weeks.…”
Section: Participantssupporting
confidence: 86%
“…Considering the fact that abdominal obesity is the key characteristic of MetS (2), it is assumed that visceral adipose tissue through increased mitochondrial oxidation of free fatty acids represents the main generator of reactive oxygen (ROS) and reactive nitrogen species (RNS) (3). Indeed, previous studies confirmed an increase in some of the oxidative stress biomarkers, as well as a decrease in the antioxidant defence system in individuals with overweight/obesity (4, 5). However, it is questionable whether all of these biomarkers can predict MetS since discrepancies in the literature exist considering the relationship between oxidative stress biomarkers and MetS and/or its components (6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16).…”
Section: Introductionmentioning
confidence: 68%
“…As well as, Many studies have supported these ndings [48][49][50]. Some studies have also reported that antioxidant capacity in obese and overweight volunteers is promoted which was postulated to be due to immune system's trying to override the present in ammation [51,52].…”
Section: Discussionmentioning
confidence: 81%